2023
DOI: 10.1155/2023/3096698
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Platelet‐Rich Plasma Versus Injectable Platelet Rich Fibrin in Facial Skin Rejuvenation

Abstract: Background/Objective. Platelet-rich plasma (PRP) has a widespread use in various indications including dermatological conditions. Injectable platelet-rich fibrin on the other hand is prepared without anticoagulants and seems to have a sustained action. This study aimed to compare PRP and PRF injection treatments for facial skin rejuvenation in terms of efficacy, patient satisfaction, and side effects. Patients and Methods. Patients who received facial intradermal injections of PRP or PRF for skin rejuvenation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Atsu N et al [17] and Vesala AM et al [11] demonstrated significant enhancements in skin texture and elasticity and reduced fine lines and wrinkles. These studies suggest that the benefits of PRF extend beyond simple tissue repair; PRF acts as a natural filler by promoting the synthesis of collagen and facilitating tissue regeneration.…”
Section: Facial Rejuvenationmentioning
confidence: 98%
See 1 more Smart Citation
“…Atsu N et al [17] and Vesala AM et al [11] demonstrated significant enhancements in skin texture and elasticity and reduced fine lines and wrinkles. These studies suggest that the benefits of PRF extend beyond simple tissue repair; PRF acts as a natural filler by promoting the synthesis of collagen and facilitating tissue regeneration.…”
Section: Facial Rejuvenationmentioning
confidence: 98%
“…Comparative analyses, particularly the study by Atsu N et al [17], revealed nuanced findings when PRF is juxtaposed with other regenerative therapies, such as platelet-rich plasma (PRP). While both treatments are derived from autologous blood and share some mechanisms of action, PRF has shown superior outcomes in specific esthetic parameters such as canthal smoothness and wrinkle reduction.…”
Section: Comparison With Other Therapiesmentioning
confidence: 99%
“…These factors contribute to decreased or hyperexpression in melanocytes, reduced fibroblast activity, and diminished collagen and elastin synthesis, leading to dermal disruption and the dysregulation of the stem cell population responsible for tissue repair [ 60 , 61 ]. Subsequent skin changes involve hyper- or hypopigmentation, skin laxity, and the development of both superficial and deep wrinkles, significantly impacting self-image and social acceptance [ 62 ]. Regarding rejuvenation, the primary goal is to counteract or minimize the aging process using either surgical or noninvasive methods.…”
Section: Aesthetic Conditionsmentioning
confidence: 99%
“…As the demand for aesthetic procedures to prevent related changes and enhance skin quality has risen, there has been a notable decline in the number of patients opting for surgical interventions [ 61 ]. Among the nonsurgical aesthetic procedures, PRP has been extensively researched and has yielded favorable results with high patient satisfaction and no significant adverse effects [ 62 ]. PRP offers numerous benefits in facial rejuvenation, addressing concerns such as atrophic acne scars, pigmentation disorders, wrinkles, folds, loss of elasticity, and tissue volume loss.…”
Section: Aesthetic Conditionsmentioning
confidence: 99%